2020
DOI: 10.1111/tmi.13361
|View full text |Cite
|
Sign up to set email alerts
|

Variation in competent and respectful delivery care in Kenya and Malawi: a retrospective analysis of national facility surveys

Abstract: objective Although substantial progress has been made in increasing access to care during childbirth, reductions in maternal and neonatal mortality have been slower. Poor-quality care may be to blame. In this study, we measure the quality of labour and delivery services in Kenya and Malawi using data from observations of deliveries and explore factors associated with levels of competent and respectful care.methods We used data from nationally representative health facility assessment surveys. A total of 1100 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…These results are concerning such that no facility type reached an average quality of care score above 56%. Frequency of performance of many items was similar to that observed in four African countries where the index was validated [24], and overall scores were slightly lower than those measured in SPA surveys including direct observation of intrapartum care in Kenya and Malawi [26]. However, quality of care was variable across health facility type and stage of labor within each facility type.…”
Section: Discussionsupporting
confidence: 62%
“…These results are concerning such that no facility type reached an average quality of care score above 56%. Frequency of performance of many items was similar to that observed in four African countries where the index was validated [24], and overall scores were slightly lower than those measured in SPA surveys including direct observation of intrapartum care in Kenya and Malawi [26]. However, quality of care was variable across health facility type and stage of labor within each facility type.…”
Section: Discussionsupporting
confidence: 62%
“…9 The quality of care provided also differs substantively across regions in Kenya with one study identifying a 25-percentage point gap between Nairobi and Coast regions. 10 Additionally, higher volume facilities and those with caesarean section capacity seemed to offer a high quality of care. 10 There have also been recent reports of increased utilisation of county-level (referral) hospitals for deliveries.…”
Section: Open Accessmentioning
confidence: 99%
“…10 Additionally, higher volume facilities and those with caesarean section capacity seemed to offer a high quality of care. 10 There have also been recent reports of increased utilisation of county-level (referral) hospitals for deliveries. 11 National assessments of quality of care at health facilities in Kenya suggest that poorer women have a higher likelihood of encountering poor quality of maternal health services in Kenya.…”
Section: Open Accessmentioning
confidence: 99%
“…Regional variations in quality of care have also been reported, with women in coastal Kenya receiving poorer quality delivery services as compared to city settings. The same study also showed that high-volume health facilities provide better quality of care [ 12 ]. Further, several studies in low and middle-income countries (LMICs), including in Kenya, have documented mistreatment and disrespect, and abuse as a challenge for women during childbirth—highlighting gaps in person-centered maternity care [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%